2008
DOI: 10.1007/bf03016090
|View full text |Cite
|
Sign up to set email alerts
|

Stability of norepinephrine infusions prepared in dextrose and normal saline solutions

Abstract: Purpose: Norepinephrine (NE) infusions are commonly used in the intensive care unit and in the operating room. Data on long term stability of NE solutions are lacking. This prospective study was designed to evaluate the stability of NE, in dextrose (5%) in water (D5W) and in normal saline (NS) solutions, for a period up to seven days. Methods: We prepared norepinephrine solutions in quadruplicate, by aseptically diluting 1 mg NE in 250 mL of D5W or NS and 4 mg NE in 250 mL of D5W or NS (final concentrations, 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(19 citation statements)
references
References 9 publications
3
16
0
Order By: Relevance
“…These results are in general agreement with all previously published studies, [5][6][7][8][9][10][11][12][13][14] which have all demonstrated the stability of norepinephrine. Of the papers published in English and reporting results obtained with stability-indicating analytical methods, 7,10-14 the study duration was relatively short, at only 24 h, 10,12,13 36 h, 7 or 7 days.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…These results are in general agreement with all previously published studies, [5][6][7][8][9][10][11][12][13][14] which have all demonstrated the stability of norepinephrine. Of the papers published in English and reporting results obtained with stability-indicating analytical methods, 7,10-14 the study duration was relatively short, at only 24 h, 10,12,13 36 h, 7 or 7 days.…”
Section: Discussionsupporting
confidence: 93%
“…11 Both Allwood 11 and Tremblay and others 14 found that norepinephrine was equally stable in dextrose and in saline solutions, in agreement with this study but in opposition to the product monograph. 4 In this study, ANOVA revealed no difference in stability due to diluent (p = 0.06).…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…Light exposure may play a certain role, but as shown by Tremblay et al, even at ambient temperature, NE solutions remain stable for 14 days when stored unprotected (Tremblay et al, 2008). Häggendal et al observed NE degradation rates of approximately 4% after 4 h in solutions stored unprotected from light and pH values above 6.0, indicating that less acidic conditions influence the stability in a non-neglectable way (Haggendal and Johnsson, 1967).…”
Section: Stability Of Epi and Ne Under Different Storage Conditions Amentioning
confidence: 92%
“…A time point was considered stable if the mean concentration of the samples exceeded 90% of the equilibrium concentration at 6 hours 710…”
Section: Methodsmentioning
confidence: 99%